2017
DOI: 10.1097/md.0000000000005835
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle screw placement accuracy of bone-mounted miniature robot system

Abstract: This article describes factors affecting the accuracy of transpedicle screw placements performed with the Renaissance robot-guided system and reviews the relevant literature. Between January 2013 and January 2015, Renaissance robot-guided spinal surgery was performed in 125 patients at Kaohsiung Medical University Hospital in Kaohsiung, Taiwan. The surgeries included 662 transpedicle screw implants and 49 Kirschner wire (K-wire) reimplants performed by intraoperative repositioning. The lead author evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…The previous studies demonstrated that the malfunction and registration failure rate of the spinal robot system was 1%, and 85.7% adverse events were related to the misoperation of surgeons. 31,32 In this way, except for keep promoting the robot system, the practice of operation skill and manipulation of the robot system are also critical to the success of robot-assisted surgery. 33 These clinical case series also explored the new pattern of "one-to-many" remote surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies demonstrated that the malfunction and registration failure rate of the spinal robot system was 1%, and 85.7% adverse events were related to the misoperation of surgeons. 31,32 In this way, except for keep promoting the robot system, the practice of operation skill and manipulation of the robot system are also critical to the success of robot-assisted surgery. 33 These clinical case series also explored the new pattern of "one-to-many" remote surgery.…”
Section: Discussionmentioning
confidence: 99%
“…At present, a variety of surgical robot systems have been used in the field of spinal surgery, including SpineAssist/Renaissance, SPINEBOT, VectorBot, and ROSA, among which the SpineAssist/Renaissance system developed in Israel is the best known. Although the SpineAssist/Renaissance spinal robot has a high accuracy of pedicle screw placement [ 11 14 ], there is still misplacement of guide wires and screws with this device [ 15 , 16 ]. In addition, SpineAssist/Renaissance has some defects, including complex operation and lack of real-time image monitoring [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pedicle screw fixation plays an important role in reconstruction procedures for spinal stability. Given the complex morphology and variability of the pedicle, screws penetrating it may injure surrounding tissues, thus resulting in severe complications in conventional spine surgery procedures, especially those involving freehand pedicle screw insertion [1][2][3][4][5]. To improve the rate of successful screw placement and reduce the complications, a robotic system for spinal surgery has been recently developed.…”
Section: Introductionmentioning
confidence: 99%